Intersectoral and multisectoral approaches to health policy: an umbrella review protocol - Michelle Amri; Ali Chatur; Patricia O'Campo (BMC, 2022)
Abstract Background It is widely recognized that one's health is influenced by a multitude of nonmedical factors, known as the social determinants of health (SDH). The SDH are defined as "the conditions in which people are born, grow, live, work and age, and which are shaped by the distribution of money, power and resources at global, national and local levels". Despite their influence on health, most of the SDH are targeted through government departments and ministries outside of the traditional health sector (e.g. education, housing). As such, the need for intersectoral and multisectoral approaches arises. Intersectoral and multisectoral approaches are thought to be essential to addressing many global health challenges our world faces today and achieving the Sustainable Development Goals. There are various ways of undertaking intersectoral and multisectoral action, but there are three widely recognized approaches (Health in All Policies [HiAP], Healthy Cities, and One Health) that each have a unique focus. However, despite the widespread acceptance of the need for intersectoral and multisectoral approaches, knowledge around how to support, achieve and sustain multisectoral action is limited. The goal of this study is to assemble evidence from systematic approaches to reviewing the literature (e.g. scoping review, systematic review) that collate findings on facilitators/enablers and barriers to implementing various intersectoral and multisectoral approaches to health, to strengthen understanding of how to best implement health policies that work across sectors, whichever they may be. Methods An umbrella review (i.e. review of reviews) is to be undertaken to collate findings from the peer-reviewed literature, specifically from Ovid MEDLINE and Scopus databases. This umbrella review protocol was developed following the preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P), and study design informed by the PRISMA guidelines for scoping reviews (PRISMA-ScR). Discussion Countries that employ multisectoral approaches are better able to identify and address issues around poverty, housing and others, by working collaboratively across sectors, with multisectoral action by governments thought to be required to achieve health equity.